Sports medicine and sailing - Allen, J. B. (Physical Medicine & Rehabilitation Clinics of North America, 1999)
Although there is little epidemiologic data in the sport of sailing, the identification of important trends can assist the clinician in successful evaluation, treatment, and rehabilitation of the individual. It appears that like other sports, the majority of injuries encountered are of the microtraumatic or overuse type. An understanding of biomechanics, the overload injury, and the sport of sailing will allow the development of a comprehensive rehabilitation program to ensure the optimal performance and safety of the sailor.